Mehdiyev , Javid - (:unkn) unknown (My University, 2026)
Javid Teymur oglu Mehdiyev graduated from the Azerbaijan University of Civil Engineers (now Azerbaijan University of Architecture and Construction – AzUAC) with a Bachelor’s degree in Applied Geodesy in 1999 and a Master’s degree in Geodesy in 2001. He began his professional career in 2000 as a Map Engineer at ShahKar in Ankara, Türkiye. From 2002 to 2004, he worked as an Assistant at the Department of Geomatics at AzUAC and has served as a Senior Lecturer at the department since 2004. From 2006 to 2015, he also worked as a Geodetic Engineer at VİRAJ LLC, participating in major engineering projects. Professor Mehdiyev has completed international professional training at NetCad in Türkiye and at Al-Farabi Kazakh National University within the Erasmus+ KA2 “GEOCLIC” project. He is the author of more than 50 scientific articles, 4 methodological guidelines, and 9 course programmes. His research focuses on the assessment of landslide processes using geodetic measurements and modern surveying technologies.